Inreraction of Syntactic Comprehension and Ability of Cognitive Sequence Processing in Persian Speeking Broca Aphasic Patients - Hayat A'meri; Arsalan Golfam; Herman Kolk; Hassan A'shayeri; Ali Mohammad Hagh-Shenas; Elliyeh Kord-Za'feranlou (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Recent studies shown that related or common neuro-physiological processes are required for processing non-linguistic structures (e.g. cognitive sequencing) and some aspects of syntactic structure in language .As there has not been such research in Iran .this study surveys the relationship between the ability to process cognitive non-linguistic abilities and comprehension of non-canonical syntactic structures in broca aphasic patients. Materials & Methods: A pre test and post test quasi experimental design was chosen in this study. The syntactic comprehension of 10 aphasic patients (6 men and 4 women) who according to the Farsi aphasic test (Nilipour.1993). Have been recognized to be broca aphasics. Was assessed before and after a training period of 10 weeks (a session every week) on cognitive sequencing. The syntactic comprehension was assessed using a test which was designed for Persian language on the basis of  test for comprehension in aphasia. The ability to process cognitive sequences was assessed using lelekov test. The subjects were selected in a purposeful manner from among the broca aphasics who were under therapy in the state speech therapy centers in Tehran. The percent of the correct answers to every syntactic structure and to the cognitive sequence for each person was measured before and after a training period of 10 weeks data were analyzed by paired-t-test.  Results: The findings showed that there is a direct relation between the ability of the patients for comprehending the non-canonical syntactic structures and their ability for processing cognitive sequencing.(R=0.50).After the training period. The ability of the patients for understanding syntactic structures with non-canonical word order improved significantly (p0.05).Their ability for processing cognitive sequencing increased significantly during the training period (P<0.05). Conclusion: Reinforcement of the ability to process complex cognitive sequences in broca aphasic patients improves their comprehension of syntactic structures with non-canonical word order but it has no effect on their comperehension of structures with canonical word order.